2013
DOI: 10.1074/jbc.m113.494922
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Tau Antibodies Targeting the 396/404 Region Are Primarily Taken Up by Neurons and Reduce Tau Protein Pathology

Abstract: Background: Tau immunotherapy is an emerging approach to treat Alzheimer disease. Results: Two novel Tau antibodies targeting the 396/404 region are primarily taken up by neurons and reduce Tau pathology. Conclusion: Receptor-mediated endocytosis and the intracellular endosome/autophagosome/lysosome system are likely involved in antibody-mediated clearance of pathological Tau. Significance: This study provides valuable insight into development of Tau immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
173
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(189 citation statements)
references
References 58 publications
13
173
3
Order By: Relevance
“…It has previously been demonstrated that antibody receptors FcγRII/III expressed on the surface of neurons in brain slices mediates uptake of uncomplexed anti-tau antibodies (24,25). The internalized antibodies are proposed to interact with cellular tau pools in a compartment that stains positive for markers of the endolysosome.…”
Section: Trim21 Is the Sole Protective Fc Receptor In A Human Neuronamentioning
confidence: 99%
“…It has previously been demonstrated that antibody receptors FcγRII/III expressed on the surface of neurons in brain slices mediates uptake of uncomplexed anti-tau antibodies (24,25). The internalized antibodies are proposed to interact with cellular tau pools in a compartment that stains positive for markers of the endolysosome.…”
Section: Trim21 Is the Sole Protective Fc Receptor In A Human Neuronamentioning
confidence: 99%
“…Moreover, antibodies against these proteins can regulate inflammation and facilitate the clearance of target proteins via autophagy or microglia (Fig. 2) [61][62][63][64][65][66]. Neurodegenerative diseases are associated with signs of chronic neuroinflammation and elevated levels of several Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For a number of years tau was considered to be purely intracellular. Sigurdsson et al reported antibodies inside neurons and proposed that antibody-mediated clearance of intracellular tau aggregates follows the lysosomal pathway [74,75]. Further studies have revealed that tau antibody uptake into neurons correlates well with tau levels.…”
Section: Targeting Taumentioning
confidence: 99%